Landasan Filosofis Pendidikan Islam: Konstruksi Tipologis Pendidikan Islam di Era Modern - Afifuddin Afifuddin; Ismail Ishak (Madrasah Tsanawiyah DDI Cilellang, 2022)
This study aims to analyze the philosophical roots of Islamic education, which are focused on four sub-problems, namely: (1) the meaning and substance of the philosophy of Islamic education; (2) the ontological; (3) the epistemological; and (4) the axiological principles of Islamic education. This research method is a literature review with a philosophical and pedagogical approach. The findings of the study indicate a close relationship between philosophy and education, namely that philosophical issues are essentially the central themes that are transferred through education and that education is a critical means in the inheritance and socialization of philosophical ideas and values. The ontological principle of Islamic education emphasizes the fundamental aspects of a belief system that revolves around the principles of purposeful creation, comprehensive unity, and solid balance. The epistemological principles of Islamic education talk about the methodological basis in an effort to transfer knowledge to students, which ultimately narrows the dichotomous gap between religious and non-religious sciences. Meanwhile, the axiological aspect of Islamic education emphasizes the actualization of absolute transcendental values and universal values that become the main basis for Islamic education materials and curriculum, which in turn form a complete Muslim person with Islamic character.